Protecting children during child protection research using administrative data - Hooper, Jade; Cusworth, Linda; Whincup, Helen (International Journal of Population Data Science, 2019)
Background with rationale Child protection systems aim to protect children from harm. Child protection research shares the same goal. However, the process of undertaking this research can present a risk. For child protection research using administrative data, children and families are at risk through breaches of privacy and identification, and further ethical issues of fair and necessary processing. This can be particularly challenging for countries such as Scotland, where smaller communities may mean children and families are more easily identifiable. For researchers and data gatekeepers alike, it is our duty to protect children in every way that we can throughout the process. Main Aim This paper aims to discuss with delegates the importance of protecting children during child protection research using administrative data, and some of the ways this can be done. Methods/Approach The paper will use an example of a recent research study which used administrative data from child protection systems in Scotland – Permanently Progressing? Building secure futures for children in Scotland. The methods used to protect children within this research and the lessons learned will be discussed. Input from delegates and the sharing of experiences will be most welcome throughout. Results and Conclusion Child protection research using administrative data often aim to inform and improve child protection systems. Such research can thereby enable more effective protection. However, such a research process raises its own child protection challenges, both to researchers and to the gatekeepers of this data. Despite this, although tricky at times to navigate, risks can be reduced through thoughtful care and consideration of these issues throughout the research process, from application to publication.